'Discovery' of non-traditional agricultural exports in Latin America: diverging pathways through learning and innovation. Issue 1 (2nd January 2018) - Iizuka, Michiko; Gebreeyesus, Mulu
ABSTRACT: Diversification of exports plays a critical role in economic growth and development, especially for countries endowed with natural resources. Successful cases often take advantage of a so-called natural resource knowledge idiosyncrasy, a unique combination of factor endowments and technological capabilities in a given natural environment. While building capabilities is fundamental, identification and exploitation of 'windows of opportunity' in the global market is of particular importance in establishing successful export industries. By examining four cases of non-traditional agricultural export products – cut flowers (Colombia and Ecuador) and blueberries (Chile and Argentina) – this paper identifies how the 'self-discovery' process of pioneers shapes the distinctive pathways through interacting with global, local and natural conditions using the adapted framework of functions of innovation systems.